Educação profissional emancipatória: possibilidades e limites de uma proposta contra-hegemônica - Amaral, Gisela Lange do (Universidade do Vale do Rio dos Sinos, 2016)
This research analyzed the context, the development and unfolding of the Course in Execution, Conservation and Restoring of Edifications – PROEJA, carried out in the Campus Pelotas of the Instituto Federal Sul-Riograndense, whose pedagogical-political project was built under a perspective of emancipatory education. It aimed at understanding its process, from planning to results, to investigate the possibilities of scooling process, on the concreteness of everyday, constituting themselves as promoters of development of critical awareness of students and, from it, its emancipation and autonomy, as condition for the participation of these subjects in the social transformation to overcome capitalism and developing relations based on principles of equality, justice and sustainability between the people and them with the planet. It is constituted of a case study articulated to presuppositions of participatory research, since the researcher takes part in the Course since its planning and, from the research, aimed at creating spaces of collective construction of the subjects who are part of it, with reflections, analysis and propositions toward qualification of its processes. The analyses were based on three key concepts: awareness, emancipation and autonomy, complemented by others, such as: hegemony contraction, reproduction, resistance, power. They were subsidized by records of participating observation and by manifestations of teachers, managers and graduated students of the Course, counterpointed to theoretical references, especially, from the area of Work and Education. It is concluded, mainly by listening to graduated students and by observing their manifestations and practices, that it is possible, and necessary, to implement of emancipatory and pedagogical proposals in public schools in which, besides being constituted in spaces of reproduction of the hegemonic social project, by contradictions which emerge in its processes, they are also spaces of resistance and, beyond it, of advances, contributing for the construction of critical awareness and emancipation of students. These results, however, depend on a set of factors of macro and micro politics, but, mainly, they are linked to the condition of autonomy and emancipation of its agents- especially, teachers and managers. At the same time, they need to be referenced to the conditions of origin of all its participants.
Keywords: Educação profissional; PROEJA; Emancipação e autonomia; Professional education; Emancipation and autonomy; ACCNPQ::Ciências Humanas::Educação